EFFECT OF HERBAL DRUGS AS A FEED ADDITIVE IN BROILER RATION - SHAILESH BHUSHAN SRIVASTAVA, D. P. SINGH, RAM NIWAS; V. K. PASWAN (The Bioscan, 2012)
A trial was conducted to determine the effect of indigenous herbal drug (Withania somnifera, Asparagus racemosus, Mucuna pruriens) supllementation in diets on performance and blood parameters in broilers. Sixty six, day old commercial broiler chicks (VenCobb 400) were divided into groups of 33 birds in each and assigned two treatment diets with three replicate of 11 broilers each. All the birds were fed basal diets and in treatment group, birds were further supplemented with 2% of indigenous herbal drug per kg feed. Experiment was conducted for 42 days. Birds that fed indigenous herbal drug in diets show the significant effect on body weight gain, feed conversion ratio and dressing percentage and decreased feed intake. There was no significant difference for SGOT, SGPT, serum protein serum glucose and serum urea between the treatments. Thus, the results show that the indigenous herbal drug having a significant efffect on the performance of the broiler chicken during summer season.